Quantitative magnetic resonance spectroscopy at 3T based on the principle of reciprocity. (21st February 2018) - Zoelch, Niklaus; Hock, Andreas; Henning, Anke
Abstract : Quantification of magnetic resonance spectroscopy signals using the phantom replacement method requires an adequate correction of differences between the acquisition of the reference signal in the phantom and the measurement in vivo. Applying the principle of reciprocity, sensitivity differences can be corrected at low field strength by measuring the RF transmitter gain needed to obtain a certain flip angle in the measured volume. However, at higher field strength the transmit sensitivity may vary from the reception sensitivity, which leads to wrongly estimated concentrations. To address this issue, a quantification approach based on the principle of reciprocity for use at 3T is proposed and validated thoroughly. In this approach, the RF transmitter gain is determined automatically using a volume‐selective power optimization and complemented with information from relative reception sensitivity maps derived from contrast‐minimized images to correct differences in transmission and reception sensitivity. In this way, a reliable measure of the local sensitivity was obtained. The proposed method is used to derive in vivo concentrations of brain metabolites and tissue water in two studies with different coil sets in a total of 40 healthy volunteers. Resulting molar concentrations are compared with results using internal water referencing (IWR) and Electric REference To access In vivo Concentrations (ERETIC). With the proposed method, changes in coil loading and regional sensitivity due to B 1 inhomogeneities are successfully corrected, as demonstrated in phantom and in vivo measurements. For the tissue water content, coefficients of variation between 2% and 3.5% were obtained (0.6–1.4% in a single subject). The coefficients of variation of the three major metabolites ranged from 3.4–14.5%. In general, the derived concentrations agree well with values estimated with IWR. Hence, the presented method is a valuable alternative for IWR, without the need for additional hardware such as ERETIC and with potential advantages in diseased tissue. Abstract : A quantification approach based on the phantom replacement method is implemented and validated in healthy volunteers. Using relative reception sensitivity maps and a volume‐selective RF power optimization, a precise correction of coil loading and reception sensitivity differences between the acquisition of the reference signal in the phantom and the measurement in vivo is possible. The molal concentrations determined agree well with values derived using the tissue water signal as a reference, implying that the method presented is a valid alternative to internal water referencing in diseased tissue.